SAT0171 RITUXIMAB IN SYSTEMIC AUTOIMMUNE RHEUMATIC DISEASES: ONE CENTER EXPERIENCE OF TREATMENT 515 PATIENTS. (2nd June 2020) - Nasonov, E.; Beketova, T.; Ananyeva, L. P.; Solovyev, S.; Vasiliev, V.; Koneva, O.; Desinova, O.; Palshina, S.; Sokol, E.; Nikollaeva, E.
Abstract : Background: B cells have important functions in the pathogenesis of systemic autoimmune rheumatic diseases (SARDs). Objectives: The purpose of the research was to study the therapeutic option of Rituximab (RTM), a chimeric anti-CD20 antibody, in SARDs such as ANCA-associated systemic vasculitis (AAV), cryoglobulinemic vasculitis (СV), systemic lupus erythematosus (SLE), systemic sclerosis (SS), primary Sjögren syndrome (pSS) and IgG4-related disease (IgG4-RD). Methods: We present data on efficacy and safety of RTM in 515 patients (pts) with SARDs. 103 pts had AAV (58- granulomatosis with polyangiitis, GPA; 35- microscopic polyangiitis, MPA and 10- eosinophilic granulomatosis with polyangiitis, EGPA), 21 pts had CV, 167- SLE, 90- SS, 100- pSS, 34- IgG4-RD. Characteristics of pts and results of RTM treatment are present in Table. Mean follow-up duration after initiation of RTM was 25- 58 months. Results: The average cumulative RTM dose in all groups exceeded 2.4 g, 71% of pts received repeated RTM courses (0.5-1.0 g) every 4 – 12 months. Complete (good) clinical response was achieved in 70-93% pts, except for the SLE (49%- complete response, 32- incomplete and 19%- no response). Usage of repeated RTM courses increased the clinical efficacy and reduced the risk of recurrence. Despite the fact that the study population included a high percentage of pts with severe or refractory SARDs, total mortality rate was about 6% during the follow-up period, highest in CV and AAV (14-11%). In AAV and SLE infections constitute a significant proportion of serious adverse reactions (10-11%). Late-onset neutropenia was only in pts with AAV (12%) and SLE (3%). Conclusion: Treatment with RTM was highly effective in SARDs. In certain SARDs RTM safety profile of should be considered during treatment planning. Further studies of the targeted anti-B-cell therapy, including RTM efficacy and safety in SARDs, clarification of the indications and optimal RTM regimens are needed. Disclosure of Interests: None declared